2009
DOI: 10.5536/kjps.2009.36.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Fatty Liver-Hemorrhagic Syndrome using Blood Biochemistry in Commercial Layers

Abstract: Fatty liver-hemorrhagic syndrome (FLHS) is a common nutritional disease in commercial layers and breeders. The most important clinical sign of FLHS is a sudden drop in egg production and increased mortality which causes significant economic loss in the poultry industry. However, the current diagnostic method for FLHS is based on the gross findings at necropsy which is not helpful to reduce the economic loss because of lateness of diagnosis. Therefore, we need early diagnosis and diagnostic methods before chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
(19 reference statements)
0
7
0
1
Order By: Relevance
“…The levels of serum GOT and GTP are a proper indicator to assay the liver and tissue damages ( Lumeij, 1997 ), and a recent study demonstrated that GOT level was significantly increased in laying hens with FLHS ( So et al, 2009 ). In the present study, there were no significant differences in serum GOT and GPT according to dietary levels of energy and lipotropic factors and estradiol benzoate treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of serum GOT and GTP are a proper indicator to assay the liver and tissue damages ( Lumeij, 1997 ), and a recent study demonstrated that GOT level was significantly increased in laying hens with FLHS ( So et al, 2009 ). In the present study, there were no significant differences in serum GOT and GPT according to dietary levels of energy and lipotropic factors and estradiol benzoate treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Commercial flocks with diseases caused higher activities of GOT in serum. Large amount of transaminase is released into blood mostly on liver cell damage ( So et al, 2009 ). Based on these findings, CBT ® administered at the levels evaluated in this study may not exert adverse effects on laying hens.…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of the serum GOT and GPT activities as indicators of liver damage in birds is a valuable tool (Lumeiji, 1997). For example, So et al (2009) found higher activities of GOT in the serum of commercial flocks with FLHS. They suggested that selected parameters of blood biochemistry, particularly GOT, could be used to diagnose FLHS before significant liver damage occurred in commercial layers.…”
Section: Effects On Lipid Parameters In Liver and Bloodmentioning
confidence: 95%